THE WATER QUALITY FROM SAINT ANA LAKE - M.VIGH; Z.MAKFALVI (Aerul şi Apa: Componente ale Mediului, 2013)
Inside the Ciomad Massive appears a unique lake in Romania, with an exclusive precipitations alimentation regime. The lake’s origin and the morphometric elements, together with the touristic activity, determine the water’s quality and characteristics. Water status evaluation was realized using random samples taken between the years 2005 and 2010. Qualitative parameters indicate the existence of a clear water lake, belonging to ultra-oligotrophic faze. This is because the crater is covered with forest and the surface erosion is very poor. Also the aquatic vegetation is rare. From all analyzed indicators, only ammonium and total mineral nitrogen have higher values during last years. In the future, the lake needs a higher protection against water quality degradation.